PENGEMBANGAN MEDIA POP-UP BOOK DIGITAL BERBASIS MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Resti Astria; Kurotul Aeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on the results of observations and interviews with grade IV teachers at SDN Ngaliyan 03 Semarang City, it was found that teachers had not used interactive learning media and the learning process that took place tended to use the lecture method. “The purpose of this study was to develop a design, determine the feasibility and effectiveness of digital pop-up book media based on the Problem Based Learning (PBL) model to improve learning outcomes of Pancasila education in grade IV Elementary Schools.”This type of research is R&D development using the Borg and Gall model modified by Sugiyono, consisting of 10 research” steps. The“researcher”only used 8 steps, due to limited time, cost, and energy. Data coIIection “techniques used test and non-test techniques.” The resuIts of the study showed that the assessment of material experts was 88.63% in the very feasible category, and media experts were 93.75% in the very feasible category. The learning media developed influenced the difference in average student learning outcomes. In large-scale product trials, the t-test calculation showed a significance value of 0.001. The results of the N-gain calculation showed a value of 0.58 in the moderate criteria.“Based on the results of the study, it can be concluded that the development of digital pop-up book media design based on the PBL model is very feasible and effective for use in the Pancasila Education learning process.”